Analisis Algoritma Greedy untuk Mewarnai Graf - Sylviani, Sisilia; Pernanda Putra, Hazel; Candra Permana, Fahmi (Diophantine Journal of Mathematics and Its Applications, 2024)
Graph coloring is one of the problems in graph theory. In graph theory, a greedy algorithm is a common algorithms in solving a problem. Greedy algorithms can be used for graph coloring; however, not all of the graph coloring problems that this algorithm uses can optimum outcomes globally. The selection of node sequencing used during the search also affects the success of the greedy algorithm in dealing with graph coloring cases. However, the use of greedy algorithms still helps reduce the number of colors used in non-directed graph coloring.